STUDY ON ESTIMATION OF FAULT PLANE AND RUPTURE DURATION FOR POTENTIAL ASSESSMENT OF TSUNAMI HAZARDS IN SOUTHWEST OF SUMATERA AND SOUTHERN PART OF WEST JAVA - Marina Utamie, Ajeng
The southwest of Sumatra and the southern part of West Java have a high potential for earthquakes and tsunamis. Several earthquakes and tsunamis in this area have caused many casualties. We use the 16 earthquake events catalog data sourced from the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) between 2009 and 2019 to estimate the fault plane and duration of fault rupture as an effort to understand the fault mechanism that causes tsunami-generating earthquakes in these areas. From the results of processing the estimated fault plane using the ISOLA and Seisgram2K programs, there are differences in earthquakes in southwest Sumatra and south of West Java. For example, in southwest Sumatra the earthquake on October 25, 2010 (Mw 7.1) in Mentawai at 01:11 UTC showed an reverse fault plane and had the largest estimated duration of fault rupture at 182.9 seconds and generated a tsunami that caused casualties and in the southern region of West Java, on the April 3, 2011 earthquake (Mw 6.6) in Tasikmalaya at 20:06 UTC, had estimated duration of fault rupture at 61.2 s and did not triggered tsunami. The results of this study are expected to be considered in efforts to mitigate earthquakes and tsunamis in the southwest of Sumatra and the southern part of West Java.